Adaptation of African swine fever virus to porcine kidney cells stably expressing CD163 and Siglec1 - Gao, Qi; Yang, Yunlong; Luo, Yizhuo; Zheng, Jiachen; Gong, Lang; Wang, Heng; Feng, Yongzhi; Gong, Ting; Wu, Dongdong; Wu, Ruixia; Zheng, Xiaoyu; Zheng, Zezhong; et al. (Frontiers in Immunology, 2022)
African swine fever virus (ASFV) is a complex large DNA enveloped virus that causes African swine fever (ASF) with a fatality rate of up to 100%, seriously threatening the global swine industry. Due to the strict cell tropism of ASFV, there is no effective in vitro cell line, which hinders its prevention and control. Herein, we analyzed genome-wide transcriptional profiles of ASFV-susceptible porcine alveolar macrophages (PAMs) and non-susceptible cell lines PK15 and 3D4-21, and found that PAM surface pattern recognition receptors (PRRs) were significantly higher and common differential genes were significantly enriched in phagocytosis compared with that observed in PK15 and 3D4-21 cell lines. Therefore, endocytosis functions of host cell surface PRRs may play key roles in ASFV infection in vitro. ASFV was found to be infective to PK15 and 3D4-21 cell lines overexpressing CD163 and Siglec1, and to the PK15S1-CD163 cell line stably expressing CD163 and Siglec1. However, the PK15 and 3D4-21 cell lines overexpressing CD163 or Siglec1 alone were not infectious. Simultaneous interference of CD163 and Siglec1 in PAMs with small interfering RNA (siRNA) significantly reduced the infectivity of ASFV. However, siRNA interference of CD163 and Siglec1 respectively did not affect ASFV infectivity. ASFV significantly inhibited IFN expression levels in PAMs and PK15S1-CD163 cells, but had no effect on PK15 and 3D4-21 cell lines. These results indicate that CD163 and Siglec1 are key receptors for ASFV-infected host cells, and both play a synergistic role in the process of ASFV infection. ASFV inhibits IFN expression in susceptible cells, thereby downregulating the host immune response and evading the immune mechanism. The discovery of the ASFV receptor provides novel ideas to study ASFV and host cell interactions, pathogenic mechanisms, development of receptor blockers, vaccine design, and disease resistance breeding.